ANALISIS KESALAHAN FONOLOGIS ARAB DALAM SERIAL DRAMA KOREA 'GENIE, MAKE A WISH' - Muhimmatul Ulumia; Setia Gumilar; Asep Supianudin; Akmaliyah Akmaliyah (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to analyze the forms and factors causing Arabic phonological errors in the Korean drama series Genie, Make a Wish. The research employs a descriptive qualitative approach with an analytical method using the distributional method and the immediate constituent technique. The data consist of Arabic dialogue utterances obtained from the Netflix platform. The results reveal phonological error categorized into four forms: consonant phoneme changes, vowel phoneme changes, phoneme omission, and phoneme addition. Consonant phoneme changes are the most dominant form of error, with the most frequent being the change of the phoneme /ق/ to /ك/ and the vowel phoneme /o/ to /a/. The main factor causing these errors is the interference of the Korean phonological system (L1) with Arabic (L2), particularly due to the absence of uvular, pharyngeal, and emphatic sounds in Korean. In addition, the limited learning process of Arabic in the context of filming production contributes to the actors’ insufficient phonological mastery when pronouncing Arabic dialogue.